Online Store Workshop Training for Micro-Business Owners to Support a Sustainable Economy - Herlianti, Anggun Oktavia; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam; Dinanti, Elpita (Fakultas Kewirausahaan Universitas Garut, 2025)
Micro entrepreneurs lack the skills to utilize digital technology, particularly in managing online stores. Most still rely on conventional marketing methods that have limited reach and are inefficient. This community service activity is implemented through a participatory and collaborative approach, prioritizing the active involvement of micro-entrepreneurs as training participants. This method is designed to build an understanding that is applicable and relevant to the real needs of entrepreneurs. The results of this training indicate a significant impact on strengthening the capacity of micro-entrepreneurs to navigate the era of economic digitalization. The results achieved not only provide short-term benefits in the form of improved technical skills but also instill sustainable values, which are essential foundations for inclusive and resilient economic development. This training also encourages participants to begin considering sustainable economic principles in running their businesses. Therefore, this training not only equips participants with digital skills but also fosters the development of an adaptive, collaborative, and responsible entrepreneurial mindset, which is highly relevant to the goal of inclusive and sustainable local economic development.